AUTOMATIC ELECTRICAL CONTROL EFFICIENCY WITH ATMEGA8 SEBAGAI INDIKATOR PEMBAYARAN DAYA LISTRIK KAMAR KOS - Prasetyo, Anang; Solihat, Solihat; Yuniar, Ningtyas (Pelita - Jurnal Penelitian Mahasiswa UNY, 2014)
The aims of the research are to design Automatic Electrical Control Efficiencywith ATMega8 as an indicator of payment and power distribution of rooms in a boardinghouse, and to reveal the effect of Automatic Electrical Control Efficiency withATMega8 as an indicator of electricity payments in a boarding house. The data obtainedfrom the survey and analysis of the condition in the field are 1) on the averagethe electricity cost is determined by the owner of the boarding house and additionalcost is given to every electronic equipment brought to the boarding house, 2) on theaverage the electricity cost for each room is 32,125.00 rupiahs with a total power ofabout 746 Watts, 3) short circuits often happen and affect other rooms, and 4) it ismostly recommended that the electricity payment is based on the power used in therooms. The result of testing the Automatic Electrical Control Efficiency with ATMega8is appropriate to implement in the boarding houses with a relatively low energymanagement. Besides, this implementation will be very helpful as a reference for themonthly transparent electricity payment based on the amount of power used.Automatic Electrical Control Efficiency with ATMega8 works by limiting the powerused in each room and the safety in each room.